Harzianic acid: a novel siderophore from Trichoderma harzianum. Issue 2 (10th September 2013) - Vinale, Francesco; Nigro, Marco; Sivasithamparam, Krishnapillai; Flematti, Gavin; Ghisalberti, Emilio L.; Ruocco, Michelina; Varlese, Rosaria; Marra, Roberta; Lanzuise, Stefania; Eid, Ahmed; Woo, Sheridan L.; Lorito, Matteo
Abstract: Agriculture‐relevant microorganisms are considered to produce secondary metabolites during processes of competition with other micro‐ and macro‐organisms, symbiosis, parasitism or pathogenesis. Many different strains of the genus Trichoderma, in addition to a direct activity against phytopathogens, are well‐known producers of secondary metabolites and compounds that substantially affect the metabolism of the host plant. Harzianic acid is a Trichoderma secondary metabolite, showing antifungal and plant growth promotion activities. This report demonstrates the ability of this tetramic acid to bind with a good affinity essential metals such as Fe 3+, which may represent a mechanism of iron solubilisation that significantly alters nutrient availability in the soil environment for other microorganisms and the host plant.